2011
DOI: 10.1161/circulationaha.110.002451
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Benefit of Statin Pretreatment in Patients Undergoing Percutaneous Coronary Intervention

Abstract: Background-Previous studies suggested that statin pretreatment reduces cardiac events in patients undergoing percutaneous coronary intervention. However, most data were observational, and single randomized trials included limited numbers of patients. Methods and Results-We performed a collaborative meta-analysis using individual patient data from 13 randomized studies in which 3341 patients received either high-dose statin (nϭ1692) or no statin/low-dose statin (nϭ1649) before percutaneous coronary intervention… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
117
2
7

Year Published

2012
2012
2022
2022

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(138 citation statements)
references
References 54 publications
11
117
2
7
Order By: Relevance
“…Supports for this hypothesis are the results of the meta-analysis of Patti et al, who found that high-dose statin pretreatment before percutaneous coronary intervention leads to a significant reduction in periprocedural myocardial infarction and 30-day adverse events. It is noteworthy that the effect is most pronounced, but is not limited in patients with elevated markers of inflammatory activity [Patti et al, 2011]. Our findings must be confirmed by larger studies.…”
Section: Discussionsupporting
confidence: 55%
“…Supports for this hypothesis are the results of the meta-analysis of Patti et al, who found that high-dose statin pretreatment before percutaneous coronary intervention leads to a significant reduction in periprocedural myocardial infarction and 30-day adverse events. It is noteworthy that the effect is most pronounced, but is not limited in patients with elevated markers of inflammatory activity [Patti et al, 2011]. Our findings must be confirmed by larger studies.…”
Section: Discussionsupporting
confidence: 55%
“…Furthermore, the Centers for Disease Control and Prevention and the American Heart Association gave the guidelines that we should use to measure hs‐CRP levels in patients who have cardiovascular risks21. Various new pharmacological approaches have been introduced to reduce hs‐CRP levels22, 23, 24, 25, 26. In order to assess the factors that largely influence hs‐CRP levels, here we examined how the accumulation of various atherosclerosis‐related risk factors influences serum hs‐CRP levels, and also tested which factors strongly influence hs‐CRP levels in patients with type 2 diabetes.…”
Section: Introductionmentioning
confidence: 99%
“…Так, в специальный метаанализ были включены ре-зультаты 13 РКИ, в которых приняли участие более 3300 пациентов [23]. Во всех исследованиях, кроме одного, включенных в этот метаанализ, ЧКВ прово-дили при стабильной стенокардии или в поздние сроки при остром коронарном синдроме (ОКС) без подъема сегмента ST. В 11-ти исследованиях пациен-там, ранее не получавшим статины, назначали пред-варительное лечение высокими дозами статинов (в сроки от 2 нед до однократной нагрузочной дозы), в других случаях больным, уже получающих посто-янную терапию статинами, назначали высокие дозы статинов.…”
Section: Fixed Combination Of Rosuvastatin and Acetylsalicylic Acid фunclassified